THE ROLE OF LOCATION DIGITALIZATION AND PROMOTIONAL VISUALIZATION TO ENCHANCE MSME VISIBILITY - Innocencia, Kesha; Tien Yustini; Reny Aziatul (Prestise: Jurnal Pengabdian Kepada Masyarakat Bidang Ekonomi dan Bisnis, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in driving both local and national economic growth. Digitalization is one of the key strategies for MSMEs to enhance competitiveness and reach wider markets. Most MSMEs in Desa Limau, Sembawa District, have not yet optimally utilized digital technology, either in business location digitalization or promotional visualization, making their businesses difficult to find and resulting in low marketing reach. This community service program aims to improve the visibility of MSMEs in Desa Limau through location digitalization and promotional visualization. The activities were carried out through direct (door-to-door) assistance, which included creating business locations on Google Maps, providing basic introductions to marketplaces (Shopee and TikTok Shop), and designing promotional banners for one of the MSMEs. Location digitalization aims to make it easier for customers to find MSME business locations online, while promotional visualization is intended to attract customer attention through both digital and physical media. The results of this training show that the door-to-door approach effectively improved MSME owners’ understanding and skills in utilizing digital technology, making business locations easier to find and promotional media more appealing. This training program is expected to serve as an initial step for MSMEs to expand their sales reach and enhance competitiveness in the digital era.